Tax justice: from distributive equity to procedural fairness in the Maghreb context - ELMAATANI Younes; ATIK Mohamed (International Journal of Scientific Research and Innovative Studies, 2026)
Tax justice is a central element in the relationship between the state and its citizens, particularly in the Maghreb countries, where taxation is associated with issues of fairness, legitimacy and institutional trust. Tax compliance depends not only on control and sanctions, but also on taxpayers' perceptions of the fairness of the system and the behavior of the administration. The literature shows a shift in approaches from distributive fairness, focused on the distribution of the tax burden, to procedural fairness, linked to transparency, consistency and respect for taxpayers. Empirical studies in the Maghreb reveal cultural constants, such as attitudes towards authority, trust in institutions and the influence of social norms, which shape tax behavior. This review emphasizes that an integrated approach, combining fairness of the tax burden and quality of administrative procedures, is essential to strengthen the legitimacy of taxation and encourage sustainable voluntary compliance. Keywords: Tax justice, Distributive fairness, Procedural fairness, Taxpayer behavior, Maghreb context Received Date: December 20, 2025 Accepted Date: January 12, 2026 Published Date: February 01, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/546